ENGLISH FOR ACADEMIC PURPOSES LEARNERS' NEEDS ANALYSIS: LANGUAGE DIFFICULTIES ENCOUNTERED BY UNIVERSITY STUDENTS IN ETHIOPIA - Sileshi Chemir; Tamene Kitila (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
The study sought to uncover the English language barriers that tertiary students faced while studying their academic courses in Ethiopia. The survey involved 421 participants (72 in the pilot research and 349 in the main research). To collect the relevant data, the researchers used a mixed-method technique. The study used probabilistic and purposive sampling techniques to choose samples from the target populations. The findings indicated that students had difficulties (e.g., in academic reading, writing, listening, and speaking) in studying their academic courses in English. The participants also indicated that current English language courses failed to encourage first-year students to improve their academic language competency to continue their studies. This happened due to a lack of thorough examination of learners' needs before creating any language curriculum. As a result, needs analysis should be viewed as the first phase to examine learners’ academic language difficulties and design EAP syllabus that caters academic language requirements of the students both in the target and learning situations.